2016
DOI: 10.1038/srep21059
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of coupled redox fuel cells using copper as electron acceptors to generate power and its in-situ retrieval

Abstract: Energy extraction from waste has attracted much interest nowadays. Herein, a coupled redox fuel cell (CRFC) device using heavy metals, such as copper, as an electron acceptor is assembled to testify the recoveries of both electricity and the precious metal without energy consumption. In this study, a NaBH4-Cu(II) CRFC was employed as an example to retrieve copper from a dilute solution with self-electricity production. The properties of the CRFC have been characterized, and the open circuit voltage was 1.65 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Many previous studies reported SEM images of electrode biofilms. 33 However, very few studies have reported the presence of filamentous appendages in the biofilms of electrodes. Many factors can be the cause of this contradiction.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies reported SEM images of electrode biofilms. 33 However, very few studies have reported the presence of filamentous appendages in the biofilms of electrodes. Many factors can be the cause of this contradiction.…”
Section: Resultsmentioning
confidence: 99%
“…Copper nanoparticles (Cu-NPs) are of great interest for applications in many engineering fields, including electronics, energy, catalyst, environment, and agriculture, owing to their natural abundance, low cost, and diversity of preparation methods [1,2]. Some (typical) examples can be mentioned such as the use of Cu-NPs in sensors [3], fuel cell, and solar cell [4,5] and in conductive inks for printed electronics [6]. In agriculture, Cu-NPs have also shown important effect in regulating plant growth and development and increasing chlorophyll formation and seed production [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, obtained OCP for GO/PPy cathode with 1000 mg/L Cu 2+ solution was much improved than 540 mV reported by Tao et al, 2011a 32 . The greater initial Cu 2+ ion concentration can provide extra electron acceptors that advance the MFC performance in terms of OCP 56 …”
Section: Resultsmentioning
confidence: 65%
“…The GO/PPy cathode catalyst electrode with 1000 mg/L Cu 2+ solution shows the higher OCP as compared to other sets. The literature reports the 0.65 V OCP for 400 mg/L Cu 2+ concentration but with 1 M KOH solution 56 . However, obtained OCP for GO/PPy cathode with 1000 mg/L Cu 2+ solution was much improved than 540 mV reported by Tao et al, 2011a 32 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation